Body mass index and incident coronary heart disease in women: a population-based prospective study - Canoy, D; Cairns, B; Balkwill, A; Wright, F; Green, J; Reeves, G; Beral, V; Study Collaborators, MW (BioMed Central, 2013)
BACKGROUND:A high body mass index (BMI) is associated with an increased risk of mortality from coronary heart disease (CHD); however, a low BMI may also be associated with an increased mortality risk. There is limited information on the relation of incident CHD risk across a wide range of BMI, particularly in women. We examined the relation between BMI and incident CHD overall and across different risk factors of the disease in the Million Women Study.METHODS:1.2 million women (mean age = 56 years) participants without heart disease, stroke, or cancer (except non-melanoma skin cancer) at baseline (1996 to 2001) were followed prospectively for 9 years on average. Adjusted relative risks and 20-year cumulative incidence from age 55 to 74 years were calculated for CHD using Cox regression.RESULTS:After excluding the first 4 years of follow-up, we found that 32,465 women had a first coronary event (hospitalization or death) during follow-up. The adjusted relative risk for incident CHD per 5 kg/m2 increase in BMI was 1.23 (95% confidence interval (CI) 1.22 to 1.25). The cumulative incidence of CHD from age 55 to 74 years increased progressively with BMI, from 1 in 11 (95% CI 1 in 10 to 12) for BMI of 20 kg/m2, to 1 in 6 (95% CI 1 in 5 to 7) for BMI of 34 kg/m2. A 10-kg/m2 increase in BMI conferred a similar risk to a 5-year increment in chronological age. The 20-year cumulative incidence increased with BMI in smokers and non-smokers, alcohol drinkers and non-drinkers, physically active and inactive, and in the upper and lower socioeconomic classes. In contrast to incident disease, the relation between BMI and CHD mortality (n = 2,431) was J-shaped. For the less than 20 kg/m2 and [greater than or equal to]35 kg/m2 BMI categories, the respective relative risks were 1.27 (95% CI 1.06 to 1.53) and 2.84 (95% CI 2.51 to 3.21) for CHD deaths, and 0.89 (95% CI 0.83 to 0.94) and 1.85 (95% CI 1.78 to 1.92) for incident CHD.CONCLUSIONS:CHD incidence in women increases progressively with BMI, an association consistently seen in different subgroups. The shape of the relation with BMI differs for incident and fatal disease.